2006
DOI: 10.3171/jns.2006.104.6.876
|View full text |Cite
|
Sign up to set email alerts
|

Gamma surgery in the treatment of nonsecretory pituitary macroadenoma

Abstract: Current experience suggests that gamma surgery is an appropriate means of managing recurrent or residual nonsecretory pituitary macroadenoma following microsurgery and a primary treatment in selected patients. To evaluate definite rates of recurrence and new endocrine deficiencies, long-term follow-up studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 58 publications
7
58
0
Order By: Relevance
“…As noted in our series of nonsecretory pituitary adenomas, with a long follow-up period, parasellar meningiomas tended to either decrease or increase compared with being unchanged in volume. 39 Cranial nerve palsies occurred in 14 (10%) of the 138 patients treated, which is consistent with previously published reports that cite cranial nerve deficits between 0% and 10% (Table 4). Factors associated with the development of cranial nerve deficits included larger tumor volume, lower peripheral radiation dose, lower maximum radiation dose, tumor progression, and longer follow-up duration.…”
Section: Discussionsupporting
confidence: 81%
“…As noted in our series of nonsecretory pituitary adenomas, with a long follow-up period, parasellar meningiomas tended to either decrease or increase compared with being unchanged in volume. 39 Cranial nerve palsies occurred in 14 (10%) of the 138 patients treated, which is consistent with previously published reports that cite cranial nerve deficits between 0% and 10% (Table 4). Factors associated with the development of cranial nerve deficits included larger tumor volume, lower peripheral radiation dose, lower maximum radiation dose, tumor progression, and longer follow-up duration.…”
Section: Discussionsupporting
confidence: 81%
“…Older fractionated radiotherapy series have reported incidences of new endocrinopathy ranging from 25% to 40%. 17,20,37,49 However, more recent multicenter radiosurgery series have reported a lower incidence of new or worsened hypopituitarism after radiosurgery that is closer to 20%, with thyroid and cortisol deficiencies reported as the most common postradiosurgical endocrinopathies. 53 Given the high incidence of adenoma progression after subtotal resection over time and the efficacy of radiosurgery for preventing tumor progression with a relatively low incidence of new endocrinopathy, the present study examines the potential utility of GKRS performed shortly after transsphenoidal surgery.…”
mentioning
confidence: 99%
“…4,14,17,20,[23][24][25][26]28,29,33,35,37,40,41,45,[47][48][49][50][51]53,56,61,63,65 While stereotactic radiosurgery confers a high rate of tumor control (approximately 90%) and a low rate of neurological deficits, the promising results of adjuvant GKRS are largely byproducts of single-center retrospective studies. 4,17,20,[23][24][25][26]28,29,33,35,37,41,45,[47][48][49]51,55,61,65 More recently, a large-scale multicenter study proposed a strong benefit-to-risk profile of GKRS for patients with recurrent or residual growing nonfunctioning pituitary adenomas. 53 Despite such findings, a prominent challenge remains in establishing...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor control rates for nonfunctioning pituitary adenomas were 87% to 97%, and the rates of new hormone deficit were 6.5% to 25% by application of margin doses of 14 to 18.5 Gy. 40,73,85,102,105) Several series of stereotactic radiosurgery for acromegaly patients showed that tumor volume control rates were 97% to 100%, insulin-like growth factor-1 normalization rates were 23% to 60% with margin doses of 15 to 27 Gy, and new hormone deficits and visual complication was observed in 12% to 34% and 0% to 4%, respectively. 41,72,108,142) In Cushing's disease, endocrine remission rates ranged from 17% to 83%.…”
Section: Benign Tumorsmentioning
confidence: 99%